EXPLORATION, ANALYSIS AND EXPLANATION OF ‘EMPLOYEE SATISFACTION’ AS AN ORGANIZATION DEVELOPMENT AND GENERAL IMPROVEMENT TOOL FOR THE IT SECTOR OF PAKISTAN - Ahsan, A.; Kiani, H. S.; Khurshid, O. (The Nucleus, 2011)
Pakistan’s IT industry is currently one of the top performers as compared to other industrial sectors within Pakistan. As per the findings of Ahsan (2008), despite the fact that Pakistan’s IT industry is competitive (with respect to other industries within Pakistan!), its true potential is yet to be unfolded. Ahsan (2008); states that Pakistan’s so called competitive IT industry has to be in lined with the international performers (Particularly South Asian economies!). A simple proof of this statement can be obtained from the fact that Pakistan’s general economy is 1/5th of Indian economy. This must be true for IT sector of both the economies, which, unfortunately is not the case because Pakistan’s IT sector is currently 1/27th of the Indian IT Sector. Ahsan (2008) believes that partial reason of this unwanted difference may be revenue models, business practices and political situations of the two countries. Other than these reasons Ahsan (2008) believes that several soft issues are also responsible for this industrial difference. Out of these soft issues ‘motivation’ is one such important factor. The role of motivation as an imperative soft issue for revitalizing workforce can also be reproduced for the discussion concerning the role of ‘basic employee satisfaction’ as an organization’s productivity and quality enhancement tool. Employees, being an integral asset of the organizations, impact organizations in accomplishment of their objectives. The impact of employee satisfaction in software industry of Pakistan is relatively less known but plays significant role. This paper analyzes the major causes of employee satisfaction and the impact of employee satisfaction on quality and productivity dimensions (particularly) in the IT organizations in Pakistan. This research presents analysis of ‘Employee Satisfaction’ for IT sector of Pakistan. The study not only explores but also presents detailed explanation and analysis of the subject area for the IT industry of Pakistan by using necessary qualitative and quantitative research methods. The paper also explains all the important issues (As identified in PhD Thesis of Ahsan) arising due to underprivileged employee satisfaction. As a result of detailed analysis performed, the paper finally identifies important recommendations for improving employee satisfaction. The study analyzes the major causes of employee satisfaction / dissatisfaction and the impact of employee satisfaction on various organizational parameters (for instance quality, productivity etc).